Chimie organique hétérocyclique : structures fondamentales, chimie et biochimie des principaux composés naturels - Milcent, René (EDP Sciences, 2003)
This work presents the basic concepts of the chemistry of inorganic chemistry. It recapitulates the courses taught to undergraduates and graduates in chemistry, physical chemistry and science of materials.